A ressignificação do projeto político-pedagógico na escola : das necessidades às ações - Costa, Gisele Maria Tonin da (2007)
The research had as objectives to investigate, get back and analyze the principal moments of the Pedagogical Political Project construction (PPP) at Santa Clara school in Getúlio Vargas-RS; to identify elements of its identity and daily pedagogical situations that cause a ressignification process; analyze the oppositions and the progresses that were noticed in the Pedagogical Political Project construction and implementation within the context that was studied and searched; discuss the ressignification process in the Pedagogical Political Project considering that its permanence is grounded in the protagonist s practice of the educational process that has been discussed. The LBD recognizes in the school a technical and political competence that qualifies it to participate in its pedagogical project elaboration. In this democratic perspective, the law widens the school s role before the society, placing it as the center of the attention in the general educational policies and suggests its autonomy support. The research characterizes itself as the study of a particular case and it s based in the biographical, documental analysis in participating observations and questionnaires. The focus that directs the research is the qualitative one. The questionnaires involved the school s direction, coordination, teachers, and staff. The theoretical referential to the theme development comes from authors that approach the Pedagogical Political Project with critical-independent perspectives. Among them: Ilma Passos A. Veiga, Paulo Freire, Elli Benincá, Moacir Gadotti, Celso dos Santos Vansconcellos. The conflict is between the ressignification and the institutional reification, where the process tends to assume a definite form. The ressignification involves a mobilization, a constant search for reflection and change. The research is presented in four chapters. The first chapter, The Pedagogical Political Project: tendencies and perspectives from the current debate , analyses the law about policies and bases- LDB 9394/96, as well as the dynamics in the context that we live and the school s role in the education of participative individuals in the Pedagogical Political Project elaboration and implementation, to make them assume the commitment to educate for citizenship, through an education that directs to creative and critical thoughts. The second chapter, Pedagogical Political Project in the school extent , discuss the importance and what the PPP means in the school extent, aiming a more significant and transforming education. The third chapter, The experience at Santa Clara School: predicaments and progresses , analyses the school PPP elaboration and development process. The forth chapter, The School s Pedagogical Political Project ressignification , deepens the different moments in the PPP construction, the tensions among the things that will be applied and the changes and ressignification possibilities.